The The Effect of Health Education Using the Think Pair Share Method on Adolescents’ Knowledge and Attitudes Regarding HIV/AIDS Prevention: Pengaruh Pendidikan Kesehatan Metode Think Pair Share terhadap Tingkat Pengetahuan dan Sikap Remaja tentang Pencegahan Hiv/Aids - Ahmadi, Furqon; Aris, Arifal; Suhariyati, Suhariyati (Jurnal Surya, 2025)
Introduction: The incidence rate of HIV/AIDS among adolescents remains significantly high in the health sector. One contributing factor is the lack of knowledge and awareness among adolescents regarding the causes and prevention of HIV/AIDS. This study aims to determine the effect of health education using the Think-pair-share  method on adolescents’ knowledge and attitudes towards HIV/AIDS prevention in Karangtinggil Village. Methods: This study used a pre-experimental design with a one-group pre-test and post-test approach. The study population included all 40 adolescents in Karangtinggil Village, selected through total sampling. Data were collected using a structured closed-ended questionnaire on knowledge and attitudes. After data tabulation, analysis was conducted using the Wilcoxon signed-rank test. Results: Adolescents who had good knowledge about HIV/AIDS prevention increased from 10% to 85%, and respondents with positive attitudes increased from 32.5% to 95%. The statistical test showed a significance level of p < 0.001 (with a significance threshold of p < 0.05). Conclusion: There is an influence of the think-pair-share  method of health education on the level of knowledge and attitudes of adolescents regarding HIV/AIDS prevention in Karangtinggil Village. Keywords: AIDS, Attitude, Health education, HIV, Knowledge, Safety (K3), Think-pair-share